Cost-Push Shocks and Monetary Policy and Monetary Policy in Open Economies - Alan Sutherland (Deutsche Bundesbank, 2002)
This paper analyses the implications of cost-push shocks for the optimal choice of monetary policy target in an two-country sticky-price model. In addition to cost-push shocks, each country is subject to labour-supply and money-demand shocks. It is shown that the fully optimal coordinated policy can be supported by independent national monetary authorities following a policy of flexible inflation targeting. A number of simple (but non-optimal) targeting rules are compared. Strict producer-price targeting is found to be the best simple rule when the variance of cost-push shocks is small. Strict consumerprice targeting is best for intermediate levels of the variance of cost-push shocks. And nominal-income targeting is best when the variance of cost-push shocks in high. In general, money-supply targeting and fixed nominal exchange rates are found to yield less welfare than these other regimes. – – Dieses Papier analysiert die Implikationen eines Cost-Push-Schocks für die optimale Wahl eines Zieles für die Geldpolitik in einem 2-Länder-Modell mit träger Preisanpassung. Neben einem Cost-Push-Schock erlebt jedes Land auch Arbeitsangebots- und Geldnachfrageschocks. Man kann sagen, dass die optimale koordinierte Politik durch unabhängige nationale Zentralbanken verwirklicht werden kann, die eine Strategie des flexiblen Inflation Targeting verfolgen. Eine Reihe einfacher (aber nicht optimaler) geldpolitischer Regeln wird verglichen. Eine Politik, bei der Ziele für die Produzentenpreise angestrebt werden, erweist sich als die beste einfache Regel, wenn die Varianz der Cost-Push-Schocks klein ist. Ziele für Konsumentenpreise sind am besten geeignet bei Cost-Push-Schocks mittlerer Stärke. Ziele für das Nominaleinkommen sind vorzuziehen, wenn die Varianz der Cost-Push-Schocks hoch ist. Im Allgemeinen sind in dem Modell Geldmengenziele oder eine Politik fester Wechselkurse wohlfahrtsökonomisch diesen genannten Regimen unterlegen.
Keywords: E58; F41; E52; 330; monetary policy; inflation targeting; welfare; Geldpolitisches Ziel; Zwei-Länder-Modell; Offene Volkswirtschaft; Geldpolitik; Wohlfahrtseffekt; Inflation Targeting; Theorie